Dietary assessment at the confluence of public and planetary health: introduction of the DIEM (Dietary Impacts on Environmental Measures) scoring system - Katz, David L.; Lindszewski, Marie; Rhee, Lauren Q.; Heller, Martin C.; Eshel, Gidon; Aronson, Dina L.; Barrett, Emily (Frontiers in Nutrition, 2025)
The environmental impacts of foods—including, notably, land use, water use, nitrogen inputs, and greenhouse gas emissions—are substantial and widely varied. Databases that quantify these separate impacts exist, but few aggregate these component measures into a consumer actionable score for the overall environmental impact of given food choices. Whereas data are readily accessible for individual food items, information about overall dietary patterns—combining individual item impacts into a unified, numerical environmental score—is less so. A means of generating an environmental impact score based on real-time dietary intake assessment and/or goal diet selection has not been established. Understanding environmental impacts at this dietary pattern level is especially relevant for informing consumer action. Leveraging available published databases for food environmental impacts and nutrient analysis, combined with novel intellectual property that stratifies dietary patterns into operationally-defined diet types and objectively measured (HEI-2020) diet quality, we developed a unified scale for environmental impacts of overall dietary pattern. We further integrated this approach into real-time dietary intake assessment and personalized goal setting. Here, we introduce the DIEM © (Dietary Impacts on Environmental Measures) scoring system, describe its development, and explore its key implications. The guiding objective is to motivate and empower consumers to reduce their personal dietary environmental footprint while improving diet quality.